Revisiting symbolic interaction in music studies and new interpretive works - Denzin, Norman K. (Bingley, U.K. : Emerald, 2014)
Addressing a perceived gap between symbolic interaction and ethnomusicological approaches to the study of music, this special issue seeks to bring the fields closer by highlighting some of the complementary theoretical constructs of phenomenology and symbolic interaction as they relate to music studies.
Introduction / Jeffrey van den Scott -- Experiencing the music : toward a visual model for the social construction of music / Jeffrey van den Scott -- Cooperative activity : the importance of audiences / David T. Bastien, Jeremy Rose -- Scenes, personae and meaning : symbolic interactionist semiotics of jazz improvisation / Scott Currie -- The scene : a conceptual template for an interactionist approach to contemporary music / Joseph A. Kotarba, Nicolas J. LaLone -- The dialectic of domination and democracy in Aeschylus's Oresteia / Gil Richard Musolf -- Wilmer's secret box : reflections on my father's life / John M. Johnson -- From biographical accounts to grounded theory : social worlds of German Trade Unions / Kirstin Bromberg -- The role of informal sport : the local context and the development of elite athletes / Vidar Halldorsson, Thorolfur Thorlindsson, Michael Katovich -- Familiar strangers : facework strategies in pursuit of nonbinding relationships in a workplace exercise group / Hilde Rossing, Susie Scott -- What to do in case of terrorism : the evolution of emergency response handbooks / Johnny Nhan, Michael A. Katovich.
Includes index.
Print version record
Keywords: Social Science -- Sociology -- General; Society & culture: general; Social theory; Symbolic interactionism; Symbolism in music